Integrating technology and social media branding to enhance sustainable tourism development through green tourism supply chains in Banten tourism villages - Kenedi, Kenedi; Nurhikmat, Mira; Anggriawan, Muhammad Angga (Universitas Merdeka Malang, 2025)
The development of sustainable tourism in rural areas increasingly relies on innovation and digital transformation. This study investigates the influence of technology adoption and social media branding on sustainable tourism, with green tourism supply chains (GTSC) acting as a mediating variable. Using a quantitative approach, data were collected from 385 respondents who are tourism stakeholders in Banten Province through a structured questionnaire. The analysis employed Structural Equation Modeling–Partial Least Squares (SEM-PLS) using SmartPLS software. The results reveal that both technology adoption and social media branding significantly influence sustainable tourism, directly and indirectly through GTSC. Social media branding had the strongest effect, followed by technology adoption. GTSC also significantly mediates the relationship between both independent variables and sustainable tourism. These findings highlight the importance of integrated strategies that combine digital innovation with green operational practices. It is recommended that tourism village stakeholders enhance digital capabilities, build green supply networks, and utilize social media strategically to support sustainability goals